A Study on Ratio Analysis in The Masulipatnam Co-operative Urban Bank Ltd. Machilipatnam, Andhra Pradesh - Prudhvi Raj, K.; Narasimha Manideep, G.A.S.R. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This paper explores the financial health of the Masulipatnam Co-operative Urban Bank at Machilipatnam through a comprehensive ratio analysis. Financial ratios serve as critical tools in evaluating a bank's performance, efficiency, and stability over time. The study focuses on key ratios such as liquidity, profitability, solvency, and efficiency, using data collected from the bank's financial reports over a selected period. The findings aim to highlight the strengths and potential financial concerns within the bank's operations and offer practical suggestions for improvement.